Analysis of Do-it-Yourself (DIY) Electrode for Soil Resistivity Measurement Practical of Geology and Geophysics Subject at Earth and Outerspace Laboratory - Cahyo Puji Asmoro; Hana Susanti (Jurnal Teknologi dan Manajemen Pengelolaan Laboratorium, 2020)
This study describes the process of designing, manufacturing and the performance of Do It Yourself (DIY) electrodes for Soil Resitivity Measurement (SRM) practicum in the Geophysical Geology course. The aim is to produce electrodes that can be used with the Geo Tester tool from the Fluke 1623. The method used was the Research and Development method. the required electrode had been analyzed prior to the idea of making make your own electrode was created. The electrodes were designed in such a way as to consider the level of accuracy, convenience, safety and economics. The results showed that the DIY electrode was made well, the limited trial of data collection using the Schlumberger and Wenner configuration methods resulted in data error values ​​of 2.43% and 4.1%, respectively. The results were much smaller than the accepted minimum error threshold, namely 20%. The validation results from DIY electrode users (Data Collection Team) and Earth Physicist lecturers gave an average rating of 3.8 out of a scale 4. Thus, DIY eceltrodes can be used in practical for Geophysical Geology lectures in the Earth and Space Laboratory